How Tycho Brahe’s recordings in 1572 support SN 1572 as a type I(a) supernova - Hinse, Tobias C.; Dorch, Bertil F.; Occhionero, Lars V. T.; Holck, Jakob P. (Frontiers in Astronomy and Space Sciences, 2023)
The 450th anniversary of the discovery of the SN 1572 supernova event was celebrated in 2022. A closer look at the historical development of the field of supernova astronomy reveals the scientific importance of Tycho Brahe’s 1572 observations of this “new star.” In their quest to learn more about the new type of stellar explosion and subsequent evolution, the initial protagonists in this field (Baader and Zwicky among others) gradually turned their attention to the final remnant state of these supernova events. Since the remnant object thought to be associated with the extragalactic supernova event was found to be very dim, the focus quickly shifted toward nearby galactic events. It is at this point where Tycho Brahe’s observations played an important and often overlooked role in the context of the development of stellar evolution as a scientific field. Tycho Brahe’s meticulous and detailed recordings of the change in brightness of the new star not only allowed modern astronomers to classify SN 1572 as a supernova event but also helped them pinpoint the exact astrometric location of SN 1572. These findings helped to empirically link extragalactic supernova events to nearby past supernova remnants in the Milky Way. This enabled subsequent observations allowing further characterization. Transforming the historical recordings to a standardized photometric system also allowed the classification of SN 1572 as a type I supernova event.